Frequency Response of an Initially Stressed Slab Made from Three Compressible Materials - DAŞDEMİR, Ahmet (Politeknik Dergisi, 2021)
In this study, the frequency response of a pre-stressed slab, which stands on a rigid foundation, subject to a timely harmonic loading was considered. The investigation is implemented according to the piecewise homogeneous body model utilizing the three-dimensional linearized theory of elastic waves in initially stressed bodies (TLTEWISB). The considered body was designed joining to three discrete slabs side-by-side. It was assumed that there exists a rigidly clamping state at all interface planes on the system. A mathematical model of the problem is constructed and the system related to equations of motion is numerically solved using the finite element method (FEM). Particularly, the effect the ratio of the layer length has on the frequency response of the slab was presented.
Keywords: Engineering; Mühendislik; Complete contact condition; compressible material; dynamic response; finite element method; initial stress